Let $f(x) = %0$. Use the definition of the derivative to calculate $f'(x)$ algebraically as follows:

$f(x) = {}$
BOX*
ACTIVEMATH
MESSAGE
BUTTONS
$f(x+h) = {}$
BOX*
Do not expand yet.
ACTIVEMATH
MESSAGE
BUTTONS
$f(x+h) - f(x) = {}$
BOX*
You need not simplify yet.
ACTIVEMATH
MESSAGE
BUTTONS
$f(x+h) - f(x) = {}$
BOX*
Expanded and simplified
ACTIVEMATH
MESSAGE
BUTTONS
$\displaystyle \frac{f(x+h) - f(x)}{h} = {}$
BOX*
ACTIVEMATH
MESSAGE
BUTTONS
$f'(x) = {}$
BOX*
ACTIVEMATH
MESSAGE
BUTTONS
In particular, $f'(%1) = {}$
BOX
MESSAGE
BUTTONS
RANDOMIZE